Purwarupa Sistem Kendali Jarak Jauh Smart Room Berbasis Smartphone - Choirul Tri Fandiansyah; Mokh. Sholihul Hadi; Resi Sari Dwijayanti Kartikasari (Universitas Merdeka Malang, 2022)
In the era of revolution 4.0 technology is developing rapidly. The control system can be integrated with new technology. Remote technology is applied in various fields. A smart room is a room that can be smartly controlled remotely. The existence of a smart room can make it easier for users to do simple work. In this study, a smart room was made with controlling lights and curtains and being able to monitor the temperature. This study uses an Android smartphone to control it. Smart room works automatically by setting a set timer via an application on an Android smartphone. Smart room prototypes can work manually and automatically. Smart room manual system via an application on an Android smartphone. In this study, the manufacture of android applications using Ionic software. The microcontroller used in designing this smart room system is using ESP WROOM 32. Utilizing the Wi-Fi feature on ESP WROOM 32 as data communication with Android smartphones.